Merangkai kembali, Dakwah NIR-Kekerasan Di Masyarakat: Metodelogi Pendidikan Agama Islam Berbasis Studi Interdisipliner - Heru Siswanto (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2017)
Religion is only used as a form of identity and group. In effect, anthropology has the potential to create bounded systems. In the end emerge psychosiologis attitude, that is in group feeling and out feeling group. Furthermore, as a strengthening identity, a religious community conducts the development of a great narrative that comes from God. As well as generating certain religious expressions on a massive scale as a form of public expose, so as to affirm the difference between religious groups with others. In other words there has been a closure of opportunities for social relations (dialogue) between religious communities. This is where there appears to be a weakening of intrapersonal intelligence, the death of a critical attitude, and the absence of a "subjective consciousness" of the faithful in expressing and preserving its religion.